REDUCTION OF SOCIAL SECURY GUARANTEES DURING CRISIS PERIOD: LEGAL EVALUATION OF THE RELATED DECISIONS - Petrylaitė, Daiva; Petrylaitė, Vida (Teisė, 2015)
Social rights and social guarantees of individuals attract a lot of attention of the legislator and of the public reaction. The article analyses the part of social guarantees, in specific, the social security benefits, which amounts and payment terms have been changed during the economic crisis. Three types of social security benefits, which were touched by the highest level, are analysed: old-age and disability pensions, unemployment benefits and sickness benefits. Although the reduction of social security benefits during the crisis was upheld and legitimate according the Constitutional Court of the Republic of Lithuania, but part of the decisions may be found not meeting the requirements of the main principles of the law. The compensation arrangements of social insurance pensions do not sufficiently provide all pension beneficiaries the right to compensation, and do not correspond the principles of justice and proportionality in the society. Actual amounts of unemployment insurance benefits and the sickness benefits during the crisis did not meet even the minimum social protection standards enshrined in the provisions of international law.